PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MOTIVASI BELAJAR SISWA KELAS IV PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI MI TARBIYATUL ISLAMIYAH KECAMATAN MEGAMENDUNG BOGOR - Iyon Muhdiyati (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2023)
The process of learning in the classroom offline provides a lot of various variations that are used to convey teaching material or materials. So that in the learning process also uses a lot of various methods or media. Learning media is a means or tool used by teachers to deliver teaching material or materials to students. Audio-visual is one of the media that presents a picture that can be seen and heard which contains materials that will later become teaching materials when the learning process takes place besides that audio-visual media for learning can be made more varied and interesting. This type of research using quantitative experiments can be used to find the effect of certain treatment variables on other variables. Data collection is one of the important stages in research. Data collection is carried out to obtain the information needed in order to achieve research objectives. The data collection techniques are observation, interviews, tests and documentation Based on the results of the research and discussion above, the researchers concluded that there was an influence of instructional video media on students' Civics learning motivation in class IV MIS Tarbiyatul Islamiyah. This is evidenced by the results of the posttest average value of the control class of 67.41 and the average value of the experimental class posttest of 70.72. The difference in motivation to learn PPKn is also proven based on the results of independent sample t-test calculations obtained a significance value of less than 0.05, namely 0.001 <0.05, which means that H0 is rejected and H1 is accepted, that is, there is an average posttest in the experimental class more than the control.